Users’ Perception towards the Adoption of Net Banking Web Face Platform in Malaysian - Ashiq, Ashiquzzaman Md; Sarwar, Abdullah; Rahman, Waliur Md (IJRDO - Journal of Business Management, 2016)
To make the banking services more convenient for their customers, banks require introducingvarious competitive services such as easier accessibility to e-payment. However, popularity ofnet banking in Malaysia is relatively low due to technophobia and negative attitudes ofcustomers towards innovative products. Therefore, this study aimed at exploring the factorsaffecting the net banking adoption among Malaysian banking customers. The result showssignificant influence of net banking on the perception of the Malaysian customers. However, netbanking uses among Malaysian customers are being affected due to the consequences of trustfactors phenomena that could be viewed as a negative sign towards the adoption of net banking.